Features of the modern course of infectious processes of the genital tract in women - Satterthwaite Z., Hollingdale T. (Open Journal of Physicians and Surgeons, 2025)
Recurrent lower urinary tract infection (LUTI) in women is a common infectious and inflammatory disease of the genitourinary system, which occurs as a result of bacterial colonization of the uroepithelial lining of the bladder and urethra with the subsequent formation of “silent” microbial intracellular reservoirs in the subepithelial layer against the background of decreased cellular immunity. Throughout life, symptoms of acute cystitis occasionally occur in 60% of women regardless of age, social and educational level. Modern diagnostic technologies, in particular, modifications of the polymerase chain reaction (PCR), have led to the identification and determination of the role of new microorganisms in the development of BV